A simplified acute kidney injury predictor following endovascular aortic repair: ACEF score. (February 2023) - Avci, Yalcin; Demir, Ali Riza; Güler, Arda; Aktemur, Tugba; Bulut, Umit; Demirci, Gökhan; Memiç Sancar, Kadriye; Ersoy, Burak; Celik, Omer; Erturk, Mehmet
Objectives: Treatment of abdominal aortic aneurysms (AAA) with endovascular aortic repair (EVAR) has become quite common in recent years. This method, which has many advantages compared to the open surgical procedure, also has some complications. One of these complications is acute kidney injury (AKI). ACEF (age, creatinine, and ejection fraction) score, which is gaining popularity, can be an easy-to-use and cost-effective method in detecting this condition that causes increased morbidity and mortality. We aimed to evaluate whether this ACEF score may predict a development of AKI in patients who underwent EVAR. Methods: A total of 133 consecutive patients with AAA who underwent EVAR were analyzed. The primary endpoint of the study was the development of AKI. The best cut-off value for the ACEF score to predict the development of AKI was calculated and according to this value, the patients were divided into two groups as those with high ACEF scores and those with low ACEF scores. ACEF score was calculated by the formula of age/EF + 1 (if baseline creatinine > 2 mg/dL). Results: After the exclusion criteria, a total of 118 patients were included in the study, and 20 (16.9%) of them developed AKI after EVAR. In the ROC curve analysis, a cut-off value of 1.34 was found for the ACEF score, and scores above this value were found to be independent predictors of AKI development after EVAR. In addition to the ACEF score, the contrast media volume was also found to be an independent predictor of the development of AKI. Conclusion: In conclusion, ACEF is a simple and effective scoring system in patients undergoing EVAR. To the best our knowledge, our study is the first study which applies ACEF score to predict AKI in EVAR patients.